Atividade antimicrobiana do extrato de geoprópolis da abelha jandaíra (melipona subnitida ducke) em salmonela sp. Isoladas de carne bovina e frango - Silva, Érica Lorenna Batista da (Universidade Federal Rural do Semi-Árido, 2021)
The purpose of this study was to evaluate the antimicrobial activity of the geopropolis extract of the Jandaíra bee (Melipona subnitida Ducke) on Salmonela sp. isolated from beef and chicken sold in the city of Mossoró/RN as an alternative to antibiotics. To conduct the experiments, samples were acquired in the form of a consumer in 30 establishments throughout the city. Sixty samples were collected, 30 of beef (soft drumstick) and 30 of chicken (breast). For detection of Salmonella sp. the procedures described in normative instruction n° 62 of 2003 were followed. Positive samples were submitted to two tests, both using the disk diffusion method. In the first, the susceptibility to antimicrobials for clinical use was evaluated and in the second, the samples were submitted to the extract of geopropolis from the Jandaíra bee, diluted in three different concentrations (100%, 75% and 50%) in order to assess their potential antimicrobial, halos ≥ 6 mm were considered positive. As a result, 18 samples were positive for Salmonella sp., 12 (20%) from chicken and 6 (10%) from beef. In the evaluation of clinical antibiotics, the results showed a resistance index of 72% (13/18) to ampicillin, 11% (2/18) to sulfamethoxazole/trimethoprim, cefoxitin and amoxicillin/clavulanic acid and 6% (1/18) ) cefotaxime. 100% were sensitive to amikacin, meropenem and chloraphenicol, 94% (17/18) to ciproflaxaxin, 89% (16/18) to sulfamethoxazole/trimethoprim, cefoxitin, cefotaxime and clavulanic amoxicillin, 83% to ceftazidime and cefepime and 28 % (5/18) to ampicillin, showed an intermediate reaction to cefepime and ceftazidime 17% (3/18) and ciprofloxaxin and cefotaxime 6% (1/18). And as a response to the geopropolis extract, in the dilutions of 100% and 75%, the halos measured an average of 8mm and in 50% they had a measure of 9mm. It is concluded that there is a need for more attention in the quality control of these meats, since the presence of Salmonella sp. in 30% (18/60) of the samples analyzed, as well as their resistance to some antibiotics tested. On the other hand, we verified that the geopropolis extract presented itself as an effective antibacterial alternative
Keywords: Problema de saúde pública; Resistência a antibióticos; Extrato de geoprópolis; Public health problem; Antibiotic resistance; Geopropolis extract; CIENCIAS AGRARIAS::MEDICINA VETERINARIA